2010
DOI: 10.1021/ef901133z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytic Performance for Dimethyl Ether Synthesis from Syngas with the Addition of Zr or Ga on a Cu−ZnO−Al2O3/γ-Al2O3 Bifunctional Catalyst

Abstract: Direct synthesis of dimethyl ether (DME) from synthesis gas was investigated on bifunctional catalysts, containing Cu-ZnO-Al 2 O 3 promoted with Zr or Ga on γ-Al 2 O 3 as a methanol dehydration catalyst. In comparison to an unpromoted bifunctional catalyst, promoted catalysts with Zr or Ga showed a higher catalytic performance and stability. The facile reducibility of copper particles with high dispersion and an appropriate acidity and electronic state of copper species are mainly responsible for the superior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…c-Al 2 O 3 was easily synthesized by using the carbon black-alumina composites, where carbon black acts as an adjusting material of the pore size and surface area of c-Al 2 O 3 . Even though the contributions of the surface area of metallic copper and acidity of solid-acid components were well reported in our previous works [7,11,12,14], the acidic and structural contribution of the easily tunable c-Al 2 O 3 structures to the catalytic activity and the dispersion of copper-containing particles were not sufficiently reported as far as we know. Therefore, the effects of the acidity and the structure of c-Al 2 O 3 derived from carbon black-alumina composites on the dispersion of Cu-ZnO-Al 2 O 3 and the catalytic activity were explained by measuring the acidity and the surface area of the hybrid catalysts with the enhanced stability of the active copper-containing particles after reaction.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…c-Al 2 O 3 was easily synthesized by using the carbon black-alumina composites, where carbon black acts as an adjusting material of the pore size and surface area of c-Al 2 O 3 . Even though the contributions of the surface area of metallic copper and acidity of solid-acid components were well reported in our previous works [7,11,12,14], the acidic and structural contribution of the easily tunable c-Al 2 O 3 structures to the catalytic activity and the dispersion of copper-containing particles were not sufficiently reported as far as we know. Therefore, the effects of the acidity and the structure of c-Al 2 O 3 derived from carbon black-alumina composites on the dispersion of Cu-ZnO-Al 2 O 3 and the catalytic activity were explained by measuring the acidity and the surface area of the hybrid catalysts with the enhanced stability of the active copper-containing particles after reaction.…”
Section: Introductionmentioning
confidence: 66%
“…The solid-acid component of alumina for the preparation of hybrid catalysts has been more generally used than zeolites because it shows a higher selectivity to DME due to its lower amount of strong acidic sites, which can possibly produce hydrocarbon byproducts by the reforming reaction of DME and (or) methanol at an uncontrolled high reaction temperature in an adiabatic condition [10,11]. In addition, the easily tunable pore size, surface area, and acid sites of alumina have been more attractive for preparing hybrid catalysts by incorporating copper-based hydrogenation catalysts [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…At present, DME is mainly produced from synthesis gas by two possible approaches. One is a two-step method including methanol synthesis from synthesis gas (1) over copperbased catalysts [8][9][10] and the subsequent methanol dehydration to DME (2) on a solid acid catalyst, such as gamma alumina (cAl 2 O 3 ) [11,12] or different zeolites [13][14][15]. The other is the direct synthesis of DME from synthesis gas in one step in the presence of a bifunctional catalyst or physically mixed catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we explore a bifunctional catalyst with mesoporous structure for one-step DME synthesis. c-Al 2 O 3 has been widely used as methanol dehydration catalyst due to its moderate acidity, low price, and easy availability [11,12]. Recently, Yuan et al reported a facile route to synthesize ordered mesoporous c-Al 2 O 3 by self-assembly of Pluronic P123 triblock copolymer and alumina precursors in ethanolic solution [19].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Because direct DME synthesis from syngas is a highly exothermic process, the generated heat needs to be transferred away from the reactor to maintain the reaction temperature. A slurry reactor is employed herein due to two advantages: good temperature control and uniform temperature distribution.…”
Section: Single-step Dme Synthesismentioning
confidence: 99%